Genome mining for lasso peptides: Past, Present, and Future - Cheung-Lee, Wai Ling (J Ind Microbiol Biotechnol, 2019)
Over the course of roughly a decade, the lasso peptide field has been transformed. Whereas new compounds were discovered infrequently via activity-driven approaches, now the vast majority of lasso peptide discovery is driven by genome mining approaches. This paper starts with a historical overview of the first genome mining approaches for lasso peptide discovery, and then covers new tools that have emerged. Several examples of novel lasso peptides that have been discovered via genome mining are presented as are examples of new enzymes found associated with lasso peptide gene clusters. Finally, the paper concludes with future directions and unsolved challenges in lasso peptide genome mining.